2020
DOI: 10.46661/ijeri.5284
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Stress Due COVID-19 Pandemic Among Employed Professional Teachers

Abstract: The unexpected occurrence of the COVID-19 outbreak has undeniably disrupted the normalcy of life. Stress has become an important concern in education since the COVID-19 outbreak. This descriptive-correlational online survey administered in August 2020 utilized the COVID-19 Perceived Stress Scale (COVID-19 PSS-10) to assess the COVID-19 perceived stress among employed Filipino teachers. Whitney U and Kruskal–Wallis tested for differences while Spearman’s rho was used to analyze correlation between variables. Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
0
5

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 75 publications
(53 citation statements)
references
References 30 publications
(5 reference statements)
7
24
0
5
Order By: Relevance
“…A study carried out after school reopening among teachers from the Basque Country (Ozamiz-Etxebarria et al, 2021) showed that levels of anxiety, depression and stress symptoms were influenced by gender, age, job stability, the level of education taught, and parental status. In the Philippines, Rabacal et al (2020) revealed a moderate impact of COVID-19 on teachers' quality of life, while Oducado et al (2020) found that more than half of the teachers surveyed experienced moderate stress related to the epidemic, but these authors focused primarily on the health factor. Otherwise, however, studies examining the relationships between instructors' adaptation to and well-being during the crisis teaching period and background variables have been scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A study carried out after school reopening among teachers from the Basque Country (Ozamiz-Etxebarria et al, 2021) showed that levels of anxiety, depression and stress symptoms were influenced by gender, age, job stability, the level of education taught, and parental status. In the Philippines, Rabacal et al (2020) revealed a moderate impact of COVID-19 on teachers' quality of life, while Oducado et al (2020) found that more than half of the teachers surveyed experienced moderate stress related to the epidemic, but these authors focused primarily on the health factor. Otherwise, however, studies examining the relationships between instructors' adaptation to and well-being during the crisis teaching period and background variables have been scarce.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Numerous teachers struggle to balance their family obligations and teaching responsibilities in the face of growing coronavirus fears. Stress and anxiety together can alter the brain in ways that make the already stressful teaching job even more tolerable ( Oducado et al., 2021 ). The abrupt transition to new home teaching requirements, compounded by coronavirus fears, creates trauma that can shift the brain from higher-order thinking to survival mode ( The COVID-19 Pandemic, 2021 ).…”
Section: Introductionmentioning
confidence: 99%
“…Fecha de recepción: 14-09-2020 Fecha de aceptación: 13-10-2020 Oducado, R. M., Rabacal, J. S. Moralista, R.B. & Tamdang, K. A.…”
unclassified